Dietary Diversity: Implications for Obesity Prevention in Adult Populations. Issue 11 (11th September 2018) - de Oliveira Otto, Marcia C.; Anderson, Cheryl A.M.; Dearborn, Jennifer L.; Ferranti, Erin P.; Mozaffarian, Dariush; Rao, Goutham; Wylie-Rosett, Judith; Lichtenstein, Alice H.
Abstract : "Eat a variety of foods, " or dietary diversity, is a widely accepted recommendation to promote a healthy, nutritionally adequate diet and to reduce the risk of major chronic diseases. However, recent evidence from observational studies suggests that greater dietary diversity is associated with suboptimal eating patterns, that is, higher intakes of processed foods, refined grains, and sugar-sweetened beverages and lower intakes of minimally processed foods, such as fish, fruits, and vegetables, and may be associated with weight gain and obesity in adult populations. This American Heart Association science advisory summarizes definitions for dietary diversity and reviews current evidence on its relationship with obesity outcomes, eating behavior, and food-based diet quality measures. Current data do not support greater dietary diversity as an effective strategy to promote healthy eating patterns and healthy body weight. Given the current state of the science on dietary diversity and the insufficient data to inform recommendations on specific aspects of dietary diversity that may be beneficial or detrimental to healthy weight, it is appropriate to promote a healthy eating pattern that emphasizes adequate intake of plant foods, protein sources, low-fat dairy products, vegetable oils, and nuts and limits consumption of sweets, sugar-sweetened beverages, and red meats.